Response of creeping bentgrass (Agrostis stolonifera) and weed species to plant growth regulators. Issue 1 (3rd March 2022) - Henry, Gerald M.; Moore, Madison; Tucker, Kevin A.
Abstract: Frequent use of plant growth regulators (PGRs) may decrease the recovery of turfgrass from wear and competition with weeds. The response of new creeping bentgrass ( Agrostis stolonifera L.) cultivars to PGRs is unknown. Therefore, we aimed to evaluate the response of several creeping bentgrass cultivars and common turfgrass weeds to PGRs. Creeping bentgrass cultivars ('Penncross', 'L‐93', '007', 'V‐8', and 'Tour Pro') and weed species – goosegrass [ Eleusine indica (L.) Gaertn.] and large crabgrass ( Digitaria sanguinalis L.) – were examined. The PGR treatments were trinexapac‐ethyl (TE) (48 and 96 g a.i. ha –1 ) and prohexadione calcium (PC) (116 and 231 g a.i. ha –1 ). Plants were cut to 2.5 cm after 2 wk, and aboveground plant tissue was weighed to obtain biomass. Only 116 g a.i. ha –1 of PC was required to regulate creeping bentgrass, although the higher rate (96 g a.i. ha –1 ) of TE was needed for moderate regulation [40–50% growth inhibition (GI)], regardless of the cultivar. Some creeping bentgrass cultivars exhibited a differential response to PGRs. The lowest response to TE (22–33% GI) was observed in 'V‐8'; however, 'V‐8' was strongly regulated by PC (79–80% GI). Neither PGR successfully regulated goosegrass (14–30% GI), regardless of the rate, but moderate regulation of large crabgrass (40–49% GI) was achieved by TE at 96 g a.i. ha –1, and PC at 116 and 231 g a.i. ha –1 . Recurrent PGR applications may shift turfgrass–weed competition dynamics towards weeds such as goosegrass; however, this effect may be PGR‐specific. Core Ideas: Prohexadione calcium regulated creeping bentgrass cultivars more than trinexapac‐ethyl. Goosegrass was not effectively regulated by prohexadione calcium or trinexapac‐ethyl. Large crabgrass regulation was similar to creeping bentgrass in response to trinexapac‐ethyl.